Surface deformation on thermocapillary convection in a binary fluid with internal heat generation and temperature dependent viscosity - Hafizah Zainal Abidin, Nurul; Fadzillah Mohd Mokhtar, Nor; Zarifah Abdul Hamid, Nur; Abdul Majid, Zanariah (International Journal of Engineering and Technology, 2018)
The effects of temperature dependent viscosity and internal heat generation on the onset of steady BÃ©nard-Marangoni convection in a horizontal binary fluid layer heated from below is investigated theoretically. The upper free surface is assumed to be deformable and the lower boundary is considered to be rigid and perfectly insulated to temperature perturbations. The asymptotic solution of the long wavelength is obtained using regular perturbation method with wave number as a perturbation parameter. It is found that the surface deformation of a binary fluid layer enhances the onset of thermocapillary convection while increasing the value of internal heat generation and temperature dependent viscosity will destabilize the binary fluid layer system.Â